2022
DOI: 10.1002/ppap.202200143
|View full text |Cite
|
Sign up to set email alerts
|

The role of metals in the deposition of long‐lived reactive oxygen and nitrogen species into the plasma‐activated liquids

Abstract: The work investigates the role of metals on the formation and stability of reactive oxygen and nitrogen species (RONS) in liquids treated with a surface-wave microwave discharge. It is demonstrated that the high reduction potential metals can quasi-neutralize the acidification induced by the plasma treatment, and thus reduce the rate of the ⟶ NO + H O + H 2 − 2 2 + products reaction. As a consequence, while in the acidified plasma-activated water the NO 2 − production vanishes with increase in the treatment ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In addition, due to the presence of NO − 2 and acidity, the low-concentration H 2 O 2 could be consumed (Reaction 20). To ensure the presence of NO − 2 and H 2 O 2 in abundance, it has been studied by retarding the acidification of PAW solution, thus impeding Reactions 20 and 21 [52]. The massive amount of long-lived RONS generated by this method could be used to provide nutrients for plant growth rather than enabling a strong bactericidal efficacy due to the lack of stronger acidity (pH < 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the presence of NO − 2 and acidity, the low-concentration H 2 O 2 could be consumed (Reaction 20). To ensure the presence of NO − 2 and H 2 O 2 in abundance, it has been studied by retarding the acidification of PAW solution, thus impeding Reactions 20 and 21 [52]. The massive amount of long-lived RONS generated by this method could be used to provide nutrients for plant growth rather than enabling a strong bactericidal efficacy due to the lack of stronger acidity (pH < 3).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Lee et al (2022) reported that H 2 O 2 was undetected in PAW via the microwave plasma system; however, ONOO − was generated as an isomer of NO − 3 . Moreover, Kutasi et al (2022) reported that adding metals, such as Mg or Zn, prior to PAW generation via a surface-wave microwave discharge can be beneficial, particularly in increasing the pH of PAW and maintain the RONS concentrations during storage.…”
Section: 4mentioning
confidence: 99%
“…Moreover, Kutasi et al. (2022) reported that adding metals, such as Mg or Zn, prior to PAW generation via a surface‐wave microwave discharge can be beneficial, particularly in increasing the pH of PAW and maintain the RONS concentrations during storage.…”
Section: Generation Of Pawmentioning
confidence: 99%
“…The measurement error was set to less than 10%. The ageing dynamics of PAW depend on the pH, which was controlled by adding metal ion concentration to the water [26,27]. The Mg ions were added by inserting a solid piece of magnesium (5 g) immediately during the plasma treatment and left in the liquid for one hour after the treatment.…”
Section: Preparing Of Plasma Activated Watermentioning
confidence: 99%